SARS Coronavirus Redux - Qing, Enya (Trends Immunol, 2020)
As an atypical pneumonia began to appear in December 2019, Zhou et al. worked with remarkable speed to identify the associated virus, determine its relationship to animal viruses, and evaluate factors conferring infection susceptibility and resistance. These foundational results are being advanced to control the current worldwide human coronavirus epidemic.